Lifetime physical activity and the risk of non-Hodgkin lymphoma - Boyle, Terry; Gallagher, R.; Gascoyne, R.; Connors, J.; Le, N.; Spinelli, J. (American Association for Cancer Research Inc, 2015)
Research regarding the association between physical activity and the risk of non-Hodgkin lymphoma (NHL) is limited and inconsistent, and few studies have investigated whether the intensity and timing of physical activity influence the association. A case-control study of NHL was conducted in British Columbia, Canada, in 2000 to 2004. Data were collected on various NHL risk factors, including moderate-intensity and vigorous-intensity physical activity performed over the lifetime. Logistic regression was used to estimate the association between physical activity and the risk of NHL. This analysis included 818 controls and 749 cases. Lifetime vigorous-intensity physical activity was inversely associated with NHL risk. Participants in the second, third, and fourth quartiles of lifetime vigorous-intensity physical activity had an approximately 25% to 30% lower risk of NHL than those in the lowest quartile [adjusted odds ratios, 0.69 (95% confidence interval [CI], 0.52-0.93); 0.68 (95% CI, 0.50-0.92); and 0.75 (95% CI, 0.55-1.01), respectively]. No consistent associations were observed for total or moderate-intensity physical activity. There were no apparent age periods in which physical activity appeared to confer a greater risk reduction. In this study, we found that lifetime vigorous-intensity physical activity was associated with a significantly reduced risk of NHL. Given this finding, more research on physical activity intensity and timing in relation to NHL risk is warranted.